Avaliação do perfil molecular inflamatório em rins de doadores de critérios estendidos - Mazeti-Felício, Camila Montoro (2016)
Background: The use of kidneys from extended criteria donors (ECD) is associated with organs of inferior quality and, therefore, a high discarding rate. Clinical and histological tools available to assess non-ideal organs and predict outcomes of ECD have conflicting results. Objectives: To evaluated differences in the intragraft cytokine genes expression in ECD and SCD (standard criteria donors) kidney biopsies (Bx) pre and post-transplant (Tx) and sought possible changes induced by immunosuppressive regimens (ISS). Methodology: SCD and ECD recipients (RTx) were randomized to tacrolimus (Tac) or everolimus (Eve) and Bx were collected pre-implantation (T0 Bx; n = 80) and after 15 (T15 Bx; n = 64) and 90 days (T90 Bx; n = 51) post-Tx. Subgroups SCD-Tac, ECD-Tac, SCD-Eve and ECD-Eve were analyzed for clinical outcomes and clinical data were correlated with intragraft gene expression. Results: Overall, ECD-Eve and ECD-Tac had inferior one-year patient survival and ECD-Tac had lower graft survival than other groups while cytomegalovirus and de novo diabetes pos-Tx were higher in patients with Tac. After one year ECD-Eve patients had higher serum creatinine than ECD-Tac (p = 0.03). Acute rejection rates were higher in Eve group regardless donor type. T0 Bx of ECD showed higher expression of MCP-1, RANTES, TGF-β1 and IL-10 when compared with SCD. TGF-β1 related to the serum creatinine at harvesting the organ while length of donor hospitalization and ECD donor type were associated with upregulation of MCP-1 and RANTES. T15 Bx of patients from both groups taking Eve had increased FOXP3 and MCP-1. RANTES were upregulated only in the SCD-Eve group. Eve was the only variable associated with upregulation of FOXP3, MCP-1 and RANTES. Molecular profiling at T90 was similar except by an increase in FOXP3 transcripts restrict to SCD-Eve group. Positive expression of FOXP3 was associated with the use of Eve and delayed graft function (DGF) with the increased expression of MCP-1 and IL -10. We subtracted from Bx T15 and T90 gene expression values obtained in Bx T0 and two distinct types of molecular profile were found to SCD and ECD. SCD kidneys showed upregulation for all molecules, except TGF-β1 regardless of the ISS system, and ECD kidneys showed negative regulatory molecules for the same, except for slight positive FOXP3 and RANTES expressions. Conclusion: Pre-implantation Bx of ECD kidneys had an inflammatory molecular profile clearly distinct from SCD, with higher expression of RANTES, MCP-1, TGF-β1 and IL-10. Post-Tx, the ISS given modifies the initial cytokine expression pattern at different time points.